THE EFFECT OF STRUCTURAL FUNDS ON REGIONAL COMPETITIVENESS IN THE NEW EU COUNTRIES: THE CASE OF ROMANIA AND BULGARIA - GLIGOR DELIA ANCA GABRIELA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2015)
In the context of internationalization and globalization of the world economy, regional competitiveness is thoroughly debated by politicians and policy makers, emphasizing measurable differences between development regions, without any clear political or conceptual framework. The process of European Union integration is a main driving force of change, aiming to increase the efficiency and competitiveness of the fragmented European economy in the face of increasing internationalization. This often exposes countries and regions with unequal resources and technology and different economic structures to international competition. Such is the case of Romania and Bulgaria, countries that after joining the European Union in 2007 were given an opportunity to recover in terms of regional competitiveness and economic growth, namely structural funds as a form of nonrefundable European financial help to disadvantaged regions of member states. This research is thus focused on underlining and analyzing the relation between structural funds’ absorption and the degree of regional competitiveness for the development regions of Romania and Bulgaria, during their first programming period, through identifying and analyzing the factors that influence regional competitiveness and the amount of structural funds absorbed. First, two competitiveness country profiles are created based on data provided by relevant international organisms and second, an impact analysis is developed using six regional competitiveness indicators, grouped into three categories (economic, social and technological). Results show that EU funds critically influence the competitiveness of Romanian and Bulgarian regions, providing reliable data for policy decision makers